Problems of intellectual property in the national security system of the country - Bryhinets, O.; Shapoval, R.; Bakhaieva, A.; Pchelin, V.; Fomenko, A. (Entrepreneurship and Sustainability Issues, 2021)
The problems of intellectual property as a component of intellectual security in the national security system of the country have been considered. A statistical analysis of the registration of intellectual property in Ukraine for 2015-2019 has been carried out. The assessment of the level of intellectual security of Ukraine has been carried out on the basis of the calculation of the integrated index of intellectual security of Ukraine, which is based on the methodology of integrated assessment, the theory of factor analysis. The results confirmed that the level of intellectual security of Ukraine is low. The integrated index is in the range of the lower limit, which indicates that the state underestimates the importance of preserving, developing and increasing intellectual potential. The low level of intellectual security of Ukraine is largely due to the destructive influence of inhibitory factors, which over time can take the form of real threats. Given the diverse nature, sources and forms of manifestation, the threats of regulatory, institutional, organizational and managerial, economic, subjective, social, global and related nature, which have a destabilizing effect on the state of intellectual security of the state have been distinguished. Special attention was focused on structuring threats to intellectual potential as a strategic resource for strengthening the economic security of Ukraine. In order to achieve the strategic goals of innovation development of the state, the Strategy of development and rational use of intellectual potential to strengthen economic security of the state has been proposed. The main purpose of this strategy consists in strengthening the economic security of Ukraine on the basis of development and rational use of intellectual potential harmonized with intellectual security threats in the economic security system of the state.